Pengembangan Buku IPA Berbasis Kearifal Lokal Jambi pada Materi Tekanan serta Getaran dan Gelombang - Jufrida, Jufrida; Basuki, Fibrika Rahmat; Xena, Anta; Hasminingsih, Pretty (Universitas Islam Negeri Raden Intan Lampung, 2019)
Abstract: This study aims to develop science books based on Jambi local wisdom and improve student learning motivation. This research was a research and development using ADDIE model. The subjects were material experts, media experts and class VIII students of SMPN 1 Muaro Jambi, totaling 30 students. The instruments used in this study were observation sheets, questionnaire needs, material and media validation sheets and student motivation questionnaires. Qualitative data were analyzed descriptively and quantitative data were analyzed using descriptive statistics. This study produced a science book based on Jambi local wisdom about the pressure and vibration and waves. Local wisdom was used as a context to explore scientific concepts. The results of the material expert validation obtained an average score of 4.5 with the category